The Study Of Religious Soul In Adolescence For The Hindu Generation To Anticipate Religious Conversion - Ni Wayan Purnamiasih; Putu Cory Candra Yhani (IAHN-TP Palangka Raya, 2024)
The social reality of interfaith relationships among teenagers and adults is often encountered in the community and frequently occurs among celebrities or public figures. The phenomenon of religious conversion from Hinduism to non-Hindu religions is not only experienced by the Hindu generation from the Balinese ethnic group but also from various ethnic groups across Indonesia. The phenomenon of religious conversion occurring among Hindu teenagers is an interesting subject to study and analyse. Therefore, this paper attempts to conceptually discuss the study of religious soul in adolescence for the Hindu generation to anticipate religious conversion by using a psychological approach. Religious conversion is generally caused by many factors such as marriage, environment, career, economy, and others. However, psychologists believe that the driving factor behind religious conversion is psychological in nature. Psychologically, the factors driving religious conversion can be grouped into two main categories: internal factors (personality and disposition) and external factors (family, environment, changes in status and roles, and poverty). The psychological state of a person who converts to another religion depends on the personality of the individual. However, in Hindu teachings, abandoning the teachings of the Vedas (religious conversion) will not lead to perfection, happiness, and the highest goal, which is moksa, in accordance with the Bhagavad Gita, XVI. 23. Efforts to anticipate religious conversion among Hindu teenagers (the Hindu generation) can be carried out in two ways. The first is through parental participation in the moral and personality education of Hinduism within the family. Parents should fulfill their duties towards their children according to the guidance of the Sarasamuccaya, 242. The second way is through non-formal education (pasraman). Keywords : Religious Conversion, Religious Spirit, Hindu’Generation